In Vivo Bioluminescence Visualization of Antitumor Effects by Human MUC1 Vaccination - Yong Hyun Jeon; Yun Choi; Hyun Joo Kim; Joo Hyun Kang; Chul Woo Kim; Jae Min Jeong; Dong Soo Lee; June-Key Chung (Molecular Imaging)
Recently, the use of a cancer deoxyribonucleic acid (DNA) vaccine encoding tumor-associated antigens has emerged as an immunotherapeutic strategy. In this study, we monitored tumor growth inhibition by pcDNA3-hMUC1 immunization in mice using optical imaging. To determine the anti-hMUC1-associated immune response generated by pcDNA3.1 or pcDNA3-hMUC1, we determined the concentration of interferon-γ (IFN-γ) protein and CD8+IFN-γ cell numbers among lymphocytes from the draining lymph nodes of mice immunized with pcDNA3.1 or pcDNA3-hMUC1. After subcutaneously injecting CT26/hMUC1-F luc into mice immunized with pcDNA3-hMUC1, we monitored in vivo tumor growth inhibition using an optical imaging method. The concentration of IFN-γ protein in pcDNA3-hMUC1 was higher than that of the pcDNA3.1 group (2.7 ⩽ 0.08 ng/mL and 1.6 ± 0.07 ng/mL, respectively, p < .001. The number of hMUC1-associated CD8+IFN-γ cells in pcDNA3-hMUC1-immunized animals was 30-fold higher than in the pcDNA3.1 group. Bioluminescent images showed tumor growth inhibition in pcDNA3-hMUC1 immunized animals up to 25 days after immunization. A good correlation ( r 2 = .9076: pcDNA3/hMUC1 group; r 2 = .7428: pcDNA3.1 group) was observed between bioluminescence signals and tumor weights in two mice in each group. We conclude that optical bioluminescent imaging offers a useful means of monitoring the antitumor effects of cancer DNA immunization in living animals.